2020
DOI: 10.1007/s00592-020-01608-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of homocysteine on the risk of coronary artery diseases in individuals with diabetes: a Mendelian randomization study

Abstract: Aims Observational studies have reported that homocysteine (Hcy) is associated with an increased risk of coronary artery disease (CAD) in individuals with diabetes, though controversy remains. The present study aimed to investigate the causal association between Hcy and CAD in individuals with diabetes. Methods A 2-sample Mendelian randomization (MR) study was designed to infer causality. Genetic summary data on the association of single nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In a meta-analysis study with diabetic patients, there was no causal association between plasma homocysteine levels and coronary artery disease. 21 However, it has been reported that homocysteine causes oxidative stress, endothelial dysfunction, vascular remodeling, and atherosclerosis by inducing the phenotypic switch of VSMCs from a contractile to a synthetic phenotype. 7 , 22 , 23 Although the relevance between homocysteine and the development of atherosclerosis is not clear, the present study suggests that the high level of homocysteine in the blood may be associated with atherosclerosis in the infrainguinal muscular arteries.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis study with diabetic patients, there was no causal association between plasma homocysteine levels and coronary artery disease. 21 However, it has been reported that homocysteine causes oxidative stress, endothelial dysfunction, vascular remodeling, and atherosclerosis by inducing the phenotypic switch of VSMCs from a contractile to a synthetic phenotype. 7 , 22 , 23 Although the relevance between homocysteine and the development of atherosclerosis is not clear, the present study suggests that the high level of homocysteine in the blood may be associated with atherosclerosis in the infrainguinal muscular arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking promoted dyslipidemia, and hyperhomocysteinemia contributed to homocysteine-associated LDL-C atherosclerosis [46]. Of note, hyperhomocysteinemia was found to not be a risk factor for coronary atherosclerotic heart disease in diabetic people [48] something that was expanded upon and confirmed via MRI analysis of several diabetic individuals [49].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of HCY can increase the risk of thrombosis, oxidative stress, and endothelial dysfunction. Some studies have found elevated HCY levels to be a risk factor for CHD (30).…”
Section: Discussionmentioning
confidence: 99%